Synthesis and characterization of ZnS@Fe3O4 fluorescent-magnetic bifunctional nanospheres - Koc, Kenan; Karakus, Baris; Rajar, Kausar; Alveroglu, Esra (Elsevier BV, 2017)
Abstract Herein, we synthesized and characterized fluorescent and super paramagnetic ZnS@Fe 3 O 4 nanospheres. First, (3-mercaptopropyl) trimethoxysilane (MPS) capped ZnS quantum dots (QDs) and SiO 2 coated Fe 3 O 4 nanoparticles were synthesized separately by using solution growth and co-precipitation techniques. After synthesis and characterization of these two nanoparticles, they were conglutinated together in a nano sized sphere. The QDs were attached to the surface of the Fe 3 O 4 nanoparticles by Si O Si bonds and so Si O Si bonds created a SiO 2 network around the nanoparticles during the formation of the ZnS@Fe 3 O 4 nanospheres. The synthesized MPS capped ZnS fluorescent QDs, SiO 2 coated magnetite super paramagnetic nanoparticles and ZnS@Fe 3 O 4 fluorescent-magnetic bifunctional nanospheres were characterized by using UV–Vis Absorption Spectroscopy, Fluorescence Spectroscopy, X-ray analysis, Vibrating Sample Magnetometer analysis, Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy, Scanning Electron Microscope and Energy-dispersive X-ray spectroscopy. ZnS@Fe 3 O 4 bifunctional nanospheres were shown to retain the magnetic properties of magnetite, while exhibiting the luminescent optical properties of ZnS nanoparticles. The combination of fluorescent and magnetic behaviors of nano composites make them useful for potential applications in the field of bio-medical and environmental.